2014
DOI: 10.1149/2.1041409jes
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Methanol Alkaline Fuel Cell Based on Poly(phenylene) Anion Exchange Membranes

Abstract: The Investigation of the performance of poly(phenylene) based anion exchange membranes (AEMs) in a direct methanol fuel cell is reported. The fuel cell performances were tested with different anode gas diffusion layers as a function of concentrations of fuel and electrolyte using two commercially available platinum catalysts supported on carbon. Normalized current density values demonstrated good performance for a poly(phenylene) AEM, with a cation consisting of six methylene spacers attached to a trimethyl am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…From Figure , it is concluded that the optimal amount of amine to be added was in the ratio of 1:8 with respect to CPPO. Janarthanan et al reported the ADMFC peak power density of 3.97 mW cm −2 in methanol with no hydroxide ion moiety in the fuel which is comparable with our present results.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…From Figure , it is concluded that the optimal amount of amine to be added was in the ratio of 1:8 with respect to CPPO. Janarthanan et al reported the ADMFC peak power density of 3.97 mW cm −2 in methanol with no hydroxide ion moiety in the fuel which is comparable with our present results.…”
Section: Resultssupporting
confidence: 93%
“…PPO is one of the widely used thermoplastic for the preparation of ion exchange membranes because of its easy accessibility, good solubility, high chemical and thermal stability . Generally, PPO is used as a precursor for the preparation of various functional polymers by chemical modification either in their aryl or benzylic positions for its use as solid polymer electrolyte.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical degradation is a concern with AEMs as both the cation species and polymer backbone are susceptible to attack by hydroxide. For this reason, many AEM polymer chemistries are under investigation, including perfluorinated AEMs that resemble perfluorinated sulfonic acid (PFSAs), polysulfone and polyphenylene based AEMs, and precast films (FEP/ETFE) irradiated to generate cation functionalities grafted on the polymer . Various cation species, including quaternary phosphonium, tertiary sulfonium, and guanidinium based compounds, are being studied for alkali stability .…”
Section: Introductionmentioning
confidence: 99%
“…All fuel cells run with this technology to date that show higher power densities use added OHions in the fuel. The ultimate aim would be to run these direct methanol fuel cells without added KOH [9]. The reason for adding hydroxide is that stoichiometrically the oxidation of methanol requires 6 OHions, the hydroxide flushes the slow moving carbonate and bicarbonate, formed from reaction of CO2 and OH -, out of the anode and it improves the anode potential as > 300 mV reduction in anode over potential is possible [5].…”
Section: Introductionmentioning
confidence: 99%